化脓性汗腺炎试验结果的核心领域. (17th September 2018) - Thorlacius, L.; Ingram, J.R.; Villumsen, B.; Esmann, S.; Kirby, J.S.; Gottlieb, A.B.; Merola, J.F.; Dellavalle, R.; Nielsen, S.M.; Christensen, R.; Garg, A.; Jemec, G.B.E.; et al.
Abstract : Linked Article: Thorlacius et al. Br J Dermatol 2018;179 :642–650